2012
DOI: 10.3945/ajcn.111.018267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of blood pressure responses to caffeine drinking

Abstract: Variability in the acute BP response to coffee may be partly explained by genetic polymorphisms of the adenosine A2A receptors and α(2)-adrenergic receptors. This trial is registered at clinicaltrials.gov as NCT01330680.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 44 publications
3
59
0
5
Order By: Relevance
“…Noordzij et al found that regular caffeine intake increases blood pressure, however when ingested through coffee, the blood pressure effect of caffeine is negligible (Noordzij et al, 2005). It has been recently suggested that variability in the acute blood pressure response to coffee may be partly explained by genetic polymorphisms of the adenosine A2A receptors and alpha(2)-adrenergic receptors (Renda et al, 2012). Of note, caffeine content of one cup of coffee can vary more than 10 fold (Bangalore et al, 2007).…”
Section: Caffeinementioning
confidence: 97%
“…Noordzij et al found that regular caffeine intake increases blood pressure, however when ingested through coffee, the blood pressure effect of caffeine is negligible (Noordzij et al, 2005). It has been recently suggested that variability in the acute blood pressure response to coffee may be partly explained by genetic polymorphisms of the adenosine A2A receptors and alpha(2)-adrenergic receptors (Renda et al, 2012). Of note, caffeine content of one cup of coffee can vary more than 10 fold (Bangalore et al, 2007).…”
Section: Caffeinementioning
confidence: 97%
“…Für Koffein wird unter anderem eine Erhöhung der Katecholaminkonzentration im Plasma beschrieben. Vermutet werden ferner eine Beeinflussung der Insulinsensitivität sowie eine Wirkung auf die Endothelfunktion und den Blutdruck [9,71,72]. Im Hinblick auf die chemische Zusammensetzung des Kaffees spielt der Herstellungsprozess -wie schon bei Kakao und Rotwein -eine entscheidende Rolle.…”
Section: Kaffeeunclassified
“…In dieser Studie konnte als Ursache der Blutdrucksteigerung durch Koffein eine Zunahme des peripheren Widerstands identifiziert werden, während es zu keiner Zunahme der kardialen Kontraktilität kam. Hierzu passen Daten, die zeigen, dass Koffein -als Adenosin-Rezeptor-Antagonist -in erster Linie eine Vasokonstriktion bewirkt[72,87]. In einer weiteren Studie konnte gezeigt werden, dass die Wirkung von Kaffee auf den Blutdruck eine ausgepräg-te Variabilität aufweist.…”
unclassified
See 1 more Smart Citation
“…Renda et al [40], in a randomized placebo-controlled crossover study in 110 male healthy habitual moderate coffee drinkers refraining from coffee for the day preceding the study, found (out of 11 gene polymorphisms analyzed) a relationship between the TT genotype of ADORA2A (rs5751876) and the change (Δ) in peak systolic BP (SBP) as well as between the ADRA2B insertion II variant and the mean and peak ΔSBP within 2 h of 3 mg/kg caffeinated coffee intake. These variants were, therefore, associated with increased SBP responses to caffeine.…”
Section: Acute Effects Of Caffeine On Bpmentioning
confidence: 99%